A whole genome assembly of Leptospermum scoparium (Myrtaceae) for mānuka research. Issue 4 (2nd October 2019) - Thrimawithana, Amali H.; Jones, Dan; Hilario, Elena; Grierson, Ella; Ngo, Hanh M.; Liachko, Ivan; Sullivan, Shawn; Bilton, Timothy P.; Jacobs, Jeanne M. E.; Bicknell, Ross; David, Charles; Deng, Cecilia; et al.
ABSTRACT: We assembled the genome of Leptospermum scoparium 'Crimson Glory' using a combination of Illumina paired-end sequencing, high-throughput chromosome conformation capture (Hi-C) and high density genetic mapping. As 'Crimson Glory' is a variety of mānuka, this is the first genome assembly for a plant species culturally recognised as a treasure (taonga) by the indigenous Māori of Aotearoa New Zealand. The mānuka genome spans a total of 297 Mbp organised in 11 pseudo-chromosomes that are syntenic with the Eucalyptus genome. A large proportion of the genome assembly corresponds to fungal and bacterial sequences, indicating the presence of an associated microbiome. A total of 31, 220 protein-coding gene models were detected throughout the genome, including genes involved in biosynthesis of biologically active phenylpropanoids, triketones and terpenes, as well as genes involved in biotic resistance. The mānuka genome sequence will help shed new light on the genetic control of unique characters such as nectar and foliage biochemical composition, flowering time and disease resistance.